Production of ginger vinegar - Leonel, Magali [UNESP]; Suman, Priscila Aparecida [UNESP]; Garcia, Emerson Loli [UNESP] (Univ Federal Lavras-ufla, 2015)
Vinegar is a food of condiments group that have great use in the food industry. This study aimed to evaluate the effects of parameters of the acetic fermentation process in the production of ginger vinegar. A suspension of ginger rhizomes with 12% of starch was subjected to enzymatic hydrolysis process to obtain hydrolyzed with 85.6% of glucose. After the alcoholic fermentation the wine was obtained with 40.3% ethanol. The acetic fermentation process of ginger alcoholic solution followed a completely randomized design in a factorial for three factors at two levels. The independent variables were: temperature, nutrients and proportion of "strong vinegar" and alcoholic solution (initial acidity). Results showed variation from 2.74 to 3.70% for dry extract and 2.13 to 2.83% for ash in vinegars. The profile of organic acids of ginger vinegars showed the presence of acetic, citric, malic and succinic acids in all treatments. The condition of 20 degrees C, initial acidity 1:1, with addition of nutrients allow obtaining good quality vinegars and higher GK yields.

O vinagre, alimento do grupo de condimentos, tem seu uso bastante difundido na indústria de alimentos. Neste trabalho, objetivou-se avaliar os efeitos de parâmetros do processo de fermentação acética na obtenção de vinagre de gengibre. Uma suspensão de rizomas de gengibre, com 12% de amido, foi submetida ao processo de hidrólise enzimática, sendo obtido o hidrolisado com 85,6% de glicose. Após o processo de fermentação alcoólica, obteve-se uma calda com 40,3% de etanol. O processo de fermentação acética da calda de gengibre seguiu o delineamento inteiramente casualizado, em esquema fatorial, para três fatores em dois níveis, tendo como variáveis independentes: a temperatura, os nutrientes e a diluição da acidez inicial da calda. Os resultados obtidos mostraram uma variação de 2,74 a 3,70% de extrato seco e de 2,13 a 2,83% de cinzas nos fermentados acéticos. O perfil de ácidos orgânicos dos vinagres de gengibre evidenciou a presença de ácido acético, ácido cítrico, ácido málico e ácido succínico em todos os tratamentos. Vinagres de boa qualidade e maiores rendimentos GK podem ser obtidos nas condições de 20ºC, acidez inicial 1:1 e adição de nutrientes
Produção de vinagre de gengibre
Keywords: Zingiber officinale; Fermentation; Ethanol; acetic acid; Zingiberofficinale; Fermentação; Etanol; Ácido acético